2019
DOI: 10.2196/10899
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Interventions for Self-Control of Unhealthy Alcohol Use: Systematic Review

Abstract: Background Unhealthy alcohol use (UAU) is one of the major causes of preventable morbidity, mortality, and associated behavioral risks worldwide. Although mobile health (mHealth) interventions can provide consumers with an effective means for self-control of UAU in a timely, ubiquitous, and cost-effective manner, to date, there is a lack of understanding about different health outcomes brought by such interventions. The core components of these interventions are also unclear. Object… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 69 publications
(433 reference statements)
2
47
0
3
Order By: Relevance
“…So konnten Sander et al in ihrer Meta-Analyse hohe Effektstärken für den präventiven Einsatz von IMIs nachweisen [9]. Auch konnte die Wirksamkeit von internetbasierten Anwendungen [18] und Anwendungen für mobile Endgeräte nachgewiesen werden [19]. Die ethischen Aspekte von IMIs bei Suchtstörungen sind jedoch bislang kaum erforscht [15].…”
Section: Merkeunclassified
See 2 more Smart Citations
“…So konnten Sander et al in ihrer Meta-Analyse hohe Effektstärken für den präventiven Einsatz von IMIs nachweisen [9]. Auch konnte die Wirksamkeit von internetbasierten Anwendungen [18] und Anwendungen für mobile Endgeräte nachgewiesen werden [19]. Die ethischen Aspekte von IMIs bei Suchtstörungen sind jedoch bislang kaum erforscht [15].…”
Section: Merkeunclassified
“…Die Wirksamkeit von IMIs hinsichtlich des Therapieerfolges bei Suchtstörungen ist relativ gut erforscht. Dabei zeigen sich positive Effekte in unterschiedlichen Behandlungsstufen [6,9,14,18,19,[25][26][27]. Gerade in der Suchtprävention wird ein großes Potential gesehen [9].…”
Section: Effectivenessunclassified
See 1 more Smart Citation
“…Text messaging has shown promise as an approach to improving health outcomes among both populations with HIV [13][14][15][16][17] and those with problematic alcohol use [18]. In a study of young adult alcohol users, an interactive text messaging intervention targeting binge drinking was associated with reductions in alcohol consumption and alcohol related injury prevalence at 6 month follow-up, relative to controls [19].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of young adult alcohol users, an interactive text messaging intervention targeting binge drinking was associated with reductions in alcohol consumption and alcohol related injury prevalence at 6 month follow-up, relative to controls [19]. Likewise, a systematic review that examined outcomes of mobile health interventions targeting unhealthy alcohol use reported that 11 out of 18 studies demonstrated benefits of these approaches on drinking outcomes including alcohol use frequency, heavy drinking days, and binge drinking [20]. Text messaging interventions for people living with HIV have been the focus of various systematic reviews and meta-analyses, confirming that these approaches improve various parameters of HIV care, particularly ART adherence [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%